Superovulation in Murrah Buffaloes - SINGH, A K; NARAYANA, K (The Indian Journal of Animal Reproduction, 2023)
Superovulation of buffaloes is a critical factor in the embryo transfer industry. Several gonadotrophins have been used to stimulate follicular development in buffaloes, with large variability in ovulatory response. The present study was done to assess the superovulatory response to pFSH in buffaloes. Nine Murrah buffaloes with a palpable corpus luteum were given intramuscular (i.m.) injection of Luprostiol 15mg (Prosolvin, lntervet, Holland) and monitered for the onset of oestrus using a companion bull. Day zero was taken as Day of oestrus.